2021
DOI: 10.1021/acs.analchem.1c01861
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Simple, and Inexpensive Spatial Patterning of Wettability in Microfluidic Devices for Double Emulsion Generation

Abstract: Water-in-oil-in-water (w/o/w) double emulsion (DE) encapsulation has been widely used as a promising platform technology for various applications in the fields of food, cosmetics, pharmacy, chemical engineering, materials science, and synthetic biology. Unfortunately, DEs formed by conventional emulsion generation approaches in most cases are highly polydisperse, making them less desirable for quantitative assays, controlled biomaterial synthesis, and entrapped ingredient release. Microfluidic devices can gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…After a 10-days incubation, the θ water of the plasma-treated PDMS is 29° when stored in water, whereas it is 80.7° when stored in the air. It indicates that the hydrophilicity of plasma-treated PDMS can be prolonged by storage in an aqueous environment, which agrees with previous results ( Liu et al, 2021 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…After a 10-days incubation, the θ water of the plasma-treated PDMS is 29° when stored in water, whereas it is 80.7° when stored in the air. It indicates that the hydrophilicity of plasma-treated PDMS can be prolonged by storage in an aqueous environment, which agrees with previous results ( Liu et al, 2021 ).…”
Section: Resultssupporting
confidence: 93%
“…These results indicate that the hydrophobicity recovers quickly at the beginning, then reaches a plateau at a much slower rate. In addition, it is known that the θ water of plasma-treated PDMS surfaces are also affected by the environment in which they are stored ( Tian et al, 2018 ; Nguyen et al, 2014 ; Yang et al, 2012 ; Zhao et al, 2012 ; Liu et al, 2021 ). To investigate this point, we compared the θ water of plasma-treated PDMS surfaces when they are stored in water and the air ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…Adhesion is the first stage of successful cell culturing after seeding, but the hydrophobic nature of PDMS generally prevents cells from adhering, therefore hindering cell proliferation. Consequently, many studies have been conducted aiming to modify PDMS into a cell-friendly surface, and it has been reported that various approaches improve cell adhesion and proliferation without causing fatal defects to cells [ 10 , 11 , 12 , 13 , 14 ]. Long et al applied a polyethylene glycol (PEG)-coated layer to increase the hydrophilicity of the PDMS microfluidic chip [ 12 ], and Cho et al coated PDMS with fibronectin, which is one of the extracellular matrix (ECM) proteins, to study the trophoblast invasion of human umbilical vein endothelial cells (HUVECs) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long et al applied a polyethylene glycol (PEG)-coated layer to increase the hydrophilicity of the PDMS microfluidic chip [ 12 ], and Cho et al coated PDMS with fibronectin, which is one of the extracellular matrix (ECM) proteins, to study the trophoblast invasion of human umbilical vein endothelial cells (HUVECs) [ 13 ]. In addition to these chemistry- and biology-based approaches, physics-based attempts to alter surface wettability, such as plasma-based treatment [ 14 ] and the application of corona discharge, have also been actively used to modify the surface hydrophobicity of PDMS [ 15 ]. Nonetheless, these modification methods have some drawbacks, such as the loss of cell stability, the recovery of the innate hydrophobic surface, or the necessity of the use of multi-step processes to coat PDMS surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Surface wettability plays a paramount role in controlling and stabilizing droplet generation. If the dispersed liquid has a higher wetting affinity to microchannels than the continuous liquid, the dispersed liquid–channel wall adhesion is promoted, retarding the generation of droplets. , In comparison, nonwetting dispersed liquids can transform the stable jet into droplet formation and squeezing, transform jetting into dripping in a T-junction, achieve a higher frequency of droplet generation, , and break into monodisperse droplets at a higher capillary number . The flow velocity in a growing dispersed droplet depends markedly on the surface wettability of the inlet channel, where vortices develop earlier in a droplet more wettable to the channel than that less wettable to the channel .…”
Section: Microfluidics-enabled Soft Manufacture Of Materialsmentioning
confidence: 99%